2011
DOI: 10.1016/j.actamat.2010.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-induced grain coarsening in nanocrystalline platinum films

Abstract: Mechanisms to explain the unique mechanical behavior of nanograined metals focus primarily on grain and grain boundary mobility. In most nanograined metal materials systems (both pure and alloyed) it has not been possible to decouple these time-and cycle-dependent contributions. In contrast, the 460 nm thick, (1 1 1) textured, nanograined platinum thin films evaluated in this work have robust grain morphologies that allow us to uniquely identify the fatigue damage accumulation processes. Unlike other reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 31 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…On the contrary, Kumar et al [409] did not observe any formation of fatigue cracks after 10 million cycles in Al thin films when deformed cyclically with maximum applied strain equal to 0.4%. Meirom et al [342] measured the Da/DN versus DK response in 1 lm thick Pt films involving either very elongated columnar grains or multiple equiaxed grains along the thickness (these two morphologies exhibit almost identical uniaxial stress strain response), see also [410]. The fatigue crack resistance was found independent of the grain morphology.…”
Section: Fatiguementioning
confidence: 95%
“…On the contrary, Kumar et al [409] did not observe any formation of fatigue cracks after 10 million cycles in Al thin films when deformed cyclically with maximum applied strain equal to 0.4%. Meirom et al [342] measured the Da/DN versus DK response in 1 lm thick Pt films involving either very elongated columnar grains or multiple equiaxed grains along the thickness (these two morphologies exhibit almost identical uniaxial stress strain response), see also [410]. The fatigue crack resistance was found independent of the grain morphology.…”
Section: Fatiguementioning
confidence: 95%
“…Further investigation indicated that tensile strains did not result from the thermoforming process, but instead were induced during insertion of the microwire mold into the preformed Parylene channel; electrodes that encountered compressive stresses did not exhibit any cracks [43]. It is important that mold-induced mechanical strains do not exceed the ultimate yield strains for the device materials (0.03 for thin film platinum [44]). In the case of these Parylene micro-cones, the strain limit was reached at a radius of curvature of ∼240 µm, obtained using finite element modeling (data not shown; fabricated cones had radii of 30-90 µm).…”
Section: Dmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44] Such mechanisms leading directly to plastic deformation were first experimentally shown in 1957 by Li et al 45,46 to be active during room temperature deformation of materials possessing low-angle GBs. Extensions to high-angle GBs where a dislocation-based description 47 is incomplete, however, have been the subject of more recent research.…”
Section: Introductionmentioning
confidence: 99%